Tafsīr or Taʾwīl? The Shaykhī Contribution to the Qurʾānīc Tradition of Nineteenth Century Iran - Chamankhah, Leila (The Muslim world, 2023)
The study of Qurʾānīc exegesis in the Shaykhī school has been widely, albeit surprisingly, neglected in modern scholarship. It is surprising because there is hardly any aspect of Shaykhīsm that has remained intact after scholars have touched upon different dimensions of the school. Considering the Qurʾān, its centrality in Islamic tradition and the different methods of reading it, what is commonly understood and accepted by the mainstream as exegesis (tafsīr) might not necessarily be a suitable label for what the Shaykhī leaders did in their very ‘distinguished’ reading and interpretation of the Book. I call it ‘distinguished’, because Shaykhī elitism remains far from any compromising effort that might reduce the complexity and convolution of an all-celestial text into a literal interpretation. From a Shaykhī perspective, any such simplified challenge would not do justice to the deep and multiple levels (buṭūn) of meaning in the Qurʾān, which need an esoteric, and at times lettrist methodology to unveil divine revelation (tanzīl). Furthermore, every word needs to be understood in consideration of the akhbār of the imāms as well. Given this, the present paper will examine a number of key writings, delving into how the Shaykhī ʿulemā have interpreted the Qurʾān from an esoteric perspective, and by so doing have left a legacy which has culminated in what I call ‘the exegetical school of Kerman’. Pertinent to this is the language of the school.1 As the paper argues, the choice of Arabic as the language of tafsīr in a Persophone context was deliberate, and in fact should be understood in the light of the Shaykhī approach that assigns understanding the Qurʾān to only a skilled few.